European clinical guidelines for Tourette Syndrome and other tic disorders. Part I: assessment - Cath, Danielle C. (Springer-Verlag, 2011)
A working group of the European Society for the Study of Tourette Syndrome (ESSTS) has developed the first European assessment guidelines of Tourette Syndrome (TS). The available literature including national guidelines was thoroughly screened and extensively discussed in the expert group of ESSTS members. Detailed clinical assessment guidelines of tic disorders and their comorbidities in both children and adults are presented. Screening methods that might be helpful and necessary for specialists’ differential diagnosis process are suggested in order to further analyse cognitive abilities, emotional functions and motor skills. Besides clinical interviews and physical examination, additional specific tools (questionnaires, checklists and neuropsychological tests) are recommended.